2017
DOI: 10.1016/j.ypmed.2017.08.017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of yoga among adults with type 2 diabetes: A systematic review and meta-analysis

Abstract: The purpose of this meta-analysis was to examine the effects of yoga for glycemic control among adults with type 2 diabetes (T2DM). Comprehensive electronic databases searches located 2559 unique studies with relevant key terms. Studies were included if they (1) evaluated a yoga intervention to promote T2DM management, (2) used a comparison group, (3) reported an objective measure of glycemic control at post-intervention, and (4) had follow-up length or post-test of at least 8 weeks from baseline. Independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(70 citation statements)
references
References 73 publications
9
61
0
Order By: Relevance
“…Further significant and beneficial yoga treatment-induced mean percentage reductions in SBP (4.33%); DBP (5.66%); and TC (1.65%) could also be observed in the present study. These findings support earlier reported beneficial cardiovascular effects of yoga 25,26 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Further significant and beneficial yoga treatment-induced mean percentage reductions in SBP (4.33%); DBP (5.66%); and TC (1.65%) could also be observed in the present study. These findings support earlier reported beneficial cardiovascular effects of yoga 25,26 .…”
Section: Discussionsupporting
confidence: 93%
“…Lifestyle management plays an essential role in the efficient control of diabetes status 6,24 . Yoga, as a lifestyle intervention has been reported to lead to beneficial health outcomes related to cardiovascular and metabolic disorders including T2D 25,26 . Based on its high reported receptivity and cost-effectiveness, yoga holds a strong potential as a lifestyle management skill in Indian scenario 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations in people with DM and cardiovascular disease have reported beneficial effects following unconventional forms of exercise, such as aquatic-based exercise, Nordic walking, specific gym-fitness activities, Yoga, Pilates, Tai Chi, and dance-based activities. Less common approaches have been shown to induce positive cardiovascular effects, also improving general well-being, social inclusion, and quality of life of the participants [141][142][143][144][145][146][147].…”
Section: Exercise As Therapy For Diabetes Mellitus: Unconventional Anmentioning
confidence: 99%
“…It is noteworthy that most studies on alternative mind-body exercise therapies have focused on Yoga and Tai Chi, highlighting their positive effects on DM management. Indeed, recent summaries of the literature concluded that both Yoga and Tai Chi interventions are highly feasible and suitable for people with DM, also allowing improvements in glycemic control, cardiovascular risk factors, and biopsychosocial outcomes [146,147].…”
Section: Exercise As Therapy For Diabetes Mellitus: Unconventional Anmentioning
confidence: 99%
“…More specifically, Yoga is found to be effective in the management of many non-communicable psychosomatic disorders. [14][15][16] Likewise, Naturopathy consists of therapies using natural elements; Hydrotherapy using water, 17 heliotherapy using sun, 18 mud therapy, 19 chromotherapy using colours, 20 magnetotherapy, 21 manipulative therapy, 22 fasting therapy, 23 diet therapy 24 (includes plant-based natural supplements), acupuncture, acupressure with reflexology, 25 etc. Naturopathy by definition is more than a system of curing aches and pains and is more a 'way of life'.…”
Section: Introductionmentioning
confidence: 99%